Insulin: A pacesetter for the shape of modern biomedical science and the Nobel Prize - Jeffrey S. Flier; C. Ronald Kahn (Elsevier, 2021)
Background: The 100th anniversary of the discovery of insulin in Toronto in 1921 is an important moment in medical and scientific history. The demonstration that an extract of dog pancreas reproducibly lowered blood glucose, initially in diabetic dogs and then in humans with type 1 diabetes, was a medical breakthrough that changed the course of what was until then a largely fatal disease. The discovery of the "activity", soon named "insulin", was widely celebrated, garnering a Nobel Prize for Banting and McLeod in 1923. Over the ensuing 100 years, research on insulin has advanced on many fronts, producing insights that have transformed our understanding of diabetes and our approach to its treatment. Scope of Review: This paper will review research on insulin that had another consequence of far broader scientific significance, by serving as a pacesetter and catalyst to bioscience research across many fields. Some of this was directly insulin-related and was also recognized by the Nobel Prize. Equally important, however, was research stimulated by the discovery of insulin that has profoundly influenced biomedical research, sometimes also recognized by the Nobel Prize and sometimes without this recognition. Major Conclusions: By reviewing some of the most notable examples of both insulin-related and insulin-stimulated research, it becomes apparent that insulin had an enormous and frequently under-appreciated impact on the course of modern bioscience.